An Old Man with Unusual Precordial Pain - Albuquerque, Polianna LMM; Costa, Larizza B; Bastos, Breno B; Albuquerque, Alex Karrel S; Vasconcelos, Deborah N; Silva, Geraldo B (Journal of Medicine, 2010)
We describe an interesting case of unusual origin of precordial pain. A 75-year-old man was admitted to the Emergency Room of José Frota Institute, Fortaleza city, Brazil, because of precordial pain and malaise, three days after eating a bread. Physical examination was unremarkable. The electrocardiogram showed diffuse upward STsegment. A chest radiography showed a foreign body (a pin) in the topography of the esophagus. Esophagoscopy was performed and the pin was removed, with improvement of the patient. Keywords: Precordial pain; Pericarditis; Foreign body; Esophageal trauma; Electrocardiogram; Esophagoscopy DOI: 10.3329/jom.v11i2.5474 J MEDICINE 2010; 11 : 200-201